Rethinking ‘risk' and self-management for chronic illness - Morden, Andrew (Palgrave Macmillan, 2012)
Self-management for chronic illness is a current high profile UK healthcare policy. Policy and clinical recommendations relating to chronic illnesses are framed within a language of lifestyle risk management. This article argues the enactment of risk within current UK self-management policy is intimately related to neo-liberal ideology and is geared towards population governance. The approach that dominates policy perspectives to ‘risk' management is critiqued for positioning people as rational subjects who calculate risk probabilities and act upon them. Furthermore this perspective fails to understand the lay person's construction and enactment of risk, their agenda and contextual needs when living with chronic illness. Of everyday relevance to lay people is the management of risk and uncertainty relating to social roles and obligations, the emotions involved when encountering the risk and uncertainty in chronic illness, and the challenges posed by social structural factors and social environments that have to be managed. Thus, clinical enactments of self-management policy would benefit from taking a more holistic view to patient need and seek to avoid solely communicating lifestyle risk factors to be self-managed.